Evolution of the crystalline structure of zirconia nanoparticles during their hydrothermal synthesis and calcination: Insights into the incorporations of hydroxyls into the lattice. Issue 8 (August 2015) - Li, Fei; Li, Yanhuai; Song, Zhongxiao; Ma, Fei; Xu, Kewei; Cui, Hong
Abstract Tetragonal and cubic zirconia nanoparticles were hydrothermally prepared and calcinated at different temperature. X-ray diffraction via Rietveld refinement is used to study the crystalline structure of nanoparticles. Results show that as-prepared tetragonal nanoparticles exhibit a crystalline structure with distorted lattice; the crystalline structure evolutes with the increasing calcination temperature and the distorted lattice is recovered after nanoparticles were calcinated at temperature higher than 900 °C. The cause for lattice distortion of tetragonal nanoparticles is discussed and is explained in term of the incorporations of hydroxyls into its lattice during preparation.